2021
DOI: 10.29052/ijehsr.v9.i2.2021.190-194
|View full text |Cite
|
Sign up to set email alerts
|

Incision and drainage versus ultrasound guided needle aspiration in the management of lactational breast abscess.

Abstract: Background: Lactational breast abscess is attributed to higher morbidities among women, specifically from developing countries. Though many treatment options are available, still consensus regarding the modality yielding the best outcome is scarce. The study's objective was to compare the outcome of lactational breast abscess following incision & drainage (ID) versus ultrasound-guided needle aspiration (USGNA). Methodology: This prospective comparative investigation was carried upon a sample of 59 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Many similar studies suggest that ultrasound guided needle aspirations are more efficient in treating breast abscess. 7,8,9 A meta-analysis performed by Fu Bing 10 in department of ultrasonography, China showed that the mean healing time and the length of scar was lesser in patients underwent ultrasound guided needle aspirations (p-value 0.000). Ranjeesh V 11 in his study concluded that healing time in Group A was 19.20 days while in Group B was 30.17 days.…”
Section: Methodsmentioning
confidence: 99%
“…Many similar studies suggest that ultrasound guided needle aspirations are more efficient in treating breast abscess. 7,8,9 A meta-analysis performed by Fu Bing 10 in department of ultrasonography, China showed that the mean healing time and the length of scar was lesser in patients underwent ultrasound guided needle aspirations (p-value 0.000). Ranjeesh V 11 in his study concluded that healing time in Group A was 19.20 days while in Group B was 30.17 days.…”
Section: Methodsmentioning
confidence: 99%